(untitled) (City: History, Culture, Society, 2017)
The article examines the place and role of museum institutions in the legal, cultural activities of representatives of the Ukrainian national movement of the Russian Empire in the late nineteenth and early twentieth centuries. The author considers that in the absence of Ukrainian state and Russian imperial policy, which denied the existence of a separate Ukrainian people, the official, authorized institutions enabled the representatives of the Ukrainian creative intelligentsia a legitimate way to spread the idea of ​​a "Ukrainian project" of nation-building. The author agrees that in promoting this project, Ukrainophiles actively used "invention of traditions" (by Eric Hobsbaum) - cultural practices of a ritual or symbolic nature that were intended to express community belonging and impart specific values ​​and behaviours. In particular: life, traditional Ukrainian clothing, a celebration of anniversaries of outstanding events or anniversaries significant for the Ukrainian movement of personalities, as well as the conscious application of Ukrainian architectural modernity (Ukrainian style) in the architecture and development of Ukrainian professional theatre. Museums as sources of information about the past of Ukrainians also fit into these practices. They were accessible to the general public and had great potential to influence the society of that time. Museum exhibitions provided ample opportunities to represent Ukrainian history and culture, and by their explicit or hidden intention, their founders had the potential to become Ukrainian national. The attempt to implement such museum projects is described in the article on the example of the activity of the Kyiv Art, Industrial and Scientific Museum and the Museum of Ukrainian Antiquities V.V. Tarnovsky at the Chernihiv Provincial Zemstvo. Analyzing both the permanent exhibitions and the exhibitions held (the First South Russian Exhibition of Handicrafts in 1906, the exhibition dedicated to the fiftieth anniversary of the death of Taras Shevchenko in 1911), the author proves that there were literally "hiding places" behind the facade of the imperial museums. National ones that could well serve to shape Ukrainian identity.